Participatory Research Engagement of Vulnerable Populations: Employing Survivor-Centered, Trauma-Informed Approaches - Selima N. Jumarali; Nkiru Nnawulezi; Samantha Royson; Carrie Lippy; Ashley N. Rivera; Ty Toopet (Journal of Participatory Research Methods)
Participatory research methods increase the quality and relevance of a study and are a key element of community practice. However, participatory methods can be difficult to employ at the outset of a research study with vulnerable, hard-to-reach populations. Intimate partner violence survivors are a particularly vulnerable population who are at increased risk of experiencing abuse-related trauma and have distinct safety-related needs. In order to engage survivor populations, researchers can employ survivor-centered, trauma-informed approaches to build trust and develop relationships that facilitate increased engagement in the research process over time. This paper outlines the methods and strategies that academic partners used to establish, increase, and maintain participatory engagement with women who experienced harm by intimate partners. The process began with a community-based, qualitative needs assessment study for survivors whose partners were in a relationship violence intervention program. In addition to responding to specific aims, this study simultaneously helped to create a pool of potential collaborators. Academic partners used member checking to establish trustworthiness of the study findings and introduce the participants to the concepts of participatory engagement. Next, researchers established an advisory group to develop practice recommendations, which ultimately led to academic and community partners co-designing a community-based dissemination project. We discuss successes and tensions inherent in the engagement process, important lessons learned, and provide recommendations for future community practice.